The role of Comprehensive Sexuality Education on Child Sexual Abuse and Teenage Pregnancy among secondary school learners - Chibuye, Stephen; Kumatongo, Brighton (International Journal of Educational Innovation and Research, 2022)
The introduction of Comprehensive Sexuality Education (CSE) in the Zambian school curriculum has raised debate among stakeholders. Despite the Ministry of Education using Comprehensive Sexuality Education as a way of reducing various challenges faced by learners with regards to their sexuality education, the effectiveness and mode of implementing CSE is a source of concern. This study sought to explore the perceptions of learners and teachers on the role of Comprehensive Sexuality Education (CSE) in reducing child sexual abuse and teenage pregnancy. The total number of 60 participants who included 40 secondary school learners and 20 secondary school teachers from two secondary schools in Kitwe District on the Copperbelt Province of Zambia. The findings revealed that 50% of the learners were of the view the CSE had failed its goal of reducing child sexual abuse. The study further indicated that 60% of the teachers and 50% of the learners agreed that CSE helped to prevent early sex and teenage pregnancies in learners. The study concluded that both teachers and learners were of the views that CSE increased awareness on child sexual abuse to learners. The study recommended the need by the Ministry of Education to promote guidance and counselling services in schools with emphasis on peer counselling and peer-led life skills education to address issues of child sexual abuse and teenage pregnancy as well as the need by teachers to implement CSE by integrating its content in currier subjects and not teaching it as standalone subject.